Depression and depressive symptoms among people living with vitiligo: findings from the cross-sectional, population-based global VALIANT survey - Khaled Ezzedine; Davinder Parsad; John E. Harris; Nanja van Geel; Jackie Gardner; Kristen Bibeau; Jessy Gao; Haobo Ren; Iltefat H. Hamzavi (Journal of Dermatological Treatment)
Purpose Vitiligo often affects quality of life and psychosocial well-being. This analysis of the population-based global Vitiligo and Life Impact Among International Communities (VALIANT) study sought to understand the impact of vitiligo on depression and depressive symptoms from the patient perspective.Materials and methods The cross-sectional survey collected information on patient demographics, clinical characteristics, mental health diagnoses, and depressive symptoms (assessed using the Patient Health Questionnaire–Depression screener [PHQ-9]) among recruited patients who reported a vitiligo diagnosis.Results Of 3541 VALIANT respondents, 24.5% reported formal diagnosis of depression, and 55.0% reported moderate-to-severe symptoms of depression per the PHQ-9. Rates of formally diagnosed depression and moderate-to-severe depressive symptoms were significantly higher in younger patients, those with Fitzpatrick skin types IV–VI (i.e. darker skin), >5% affected body surface area, hand or face involvement, and those receiving mental healthcare versus their counterparts (all p < 0.0001). Interestingly, moderate-to-severe depressive symptoms were more common among patients with shorter disease duration (≤2 vs 3–9 and ≥10 years; p < 0.01), but there was no correlation between diagnosed depression and disease duration.Conclusions These VALIANT study findings highlight that depression may be common but often undiagnosed among patients with vitiligo, reinforcing the importance of an improved and multifaceted approach to vitiligo management.